A phosphorus-free scale inhibitor and dispersant for coal gasification ash water and its preparation method
Through phosphorus-free polyepoxysuccinic acid, modified scale inhibitor and zinc sulfate and other raw materials, a modified scale inhibitor is prepared. The modified scale inhibitor uses a modified copolymer as a matrix and has included substances through covalent bonds, which solves the problem of phosphorus-containing and insufficient scale inhibition performance of coal gasified ash water scale inhibitor in the prior art, and achieves efficient scale inhibition and high temperature corrosion resistance.
Patent Information
- Application Number
- CN202410972847.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-07-19
AI Technical Summary
The existing coal gasified ash water scale inhibiting dispersants contain phosphorus and have insufficient scale resistance, and are difficult to meet the resistance requirements under high temperature conditions.
Using phosphorus-free polyepoxysuccinic acid, modified scale inhibitor and zinc sulfate and other raw materials, a modified scale inhibitor is prepared through specific process steps. The modified scale inhibitor is based on the modified copolymer as the matrix and is connected with the inclusion substance through covalent bonds. The inclusion substance is a host-guest structure made by intermediate 2 with cyclodextrin as the main body as the guest.
The phosphorus-free scale resistance effect is achieved, the scale resistance performance and high temperature corrosion resistance are improved, and the pipeline scale and blockage can be effectively prevented under high temperature conditions.
Smart Images

Figure BDA0004953721300000101 
Figure BDA0004953721300000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of scale inhibitors and dispersants, and in particular to a phosphorus-free scale inhibitor and dispersant for coal gasification ash water and a preparation method thereof. Background Art
[0002] The water system of the coal gasification unit is one of the important links to ensure the stable and long-term operation of the gasifier. The pressure of the water system of the coal gasification unit is 4.0MPa-8.0MPa, and the temperature is 150℃-250℃. The circulating ash water is high hardness, high alkalinity, and has a wide pH range and is prone to scaling. During the operation of the unit, it is often accompanied by problems such as scaling, blockage and corrosion of the pipeline.
[0003] The commonly used method to solve the scaling problem of ash water in coal gasification equipment is to add scale inhibitors and dispersants. At present, there are two main types of scale inhibitors on the market: phosphoric acid and carboxylic acid. Although phosphoric acid scale inhibitors have good scale inhibition performance, they contain phosphorus, a nutrient element that makes water eutrophic, which can cause red tides. The scale inhibition performance of carboxylic acid scale inhibitors is gradually unable to meet industrial needs, and the high temperature of the ash water itself also places certain requirements on the high temperature resistance of the scale inhibitor. Summary of the invention
[0004] The purpose of the present invention is to provide a phosphorus-free scale inhibitor dispersant for coal gasification ash water and a preparation method thereof, which solves the problems of phosphorus content and insufficient scale inhibition performance of existing coal gasification ash water scale inhibitor dispersants, and also has good high temperature resistance and corrosion inhibition ability.
[0005] The purpose of the present invention can be achieved by the following technical scheme: a non-phosphorus scale inhibitor dispersant for coal gasification ash water is prepared by the following steps: weighing the following raw materials in weight percentage: 15-20% of polyepoxysuccinic acid, 10-15% of modified scale inhibitor and 2-3% of zinc sulfate, the balance being water, and mixing the polyepoxysuccinic acid, modified scale inhibitor, zinc sulfate and water to prepare a non-phosphorus scale inhibitor dispersant for coal gasification ash water;
[0006] The modified antiscalant is prepared by the following steps:
[0007] Step A1: 1-bromoadamantane, 2-methylimidazole, potassium carbonate and o-dichlorobenzene are mixed, and the mixture is reacted for 2-3 hours at a stirring rate of 300-400 rpm and a temperature of 180° C. to obtain intermediate 1; intermediate 1 is mixed with ethyl bromide, and the mixture is reacted for 20-24 hours at a stirring rate of 300-400 rpm and a temperature of 40° C. to obtain intermediate 2;
[0008] The ratio of 1-bromoadamantane, 2-methylimidazole and potassium carbonate is 0.05-0.07 mol: 0.1-0.12 mol: 15-18 g, and the ratio of intermediate 1 and ethyl bromide is 0.05-0.07 mol: 0.05-0.07 mol;
[0009] During the reaction, bromine in 1-bromoadamantane undergoes a substitution reaction with the secondary amine group at position 1 in 2-methylimidazole to obtain intermediate 1, and the tertiary amine group at position 3 of the methylimidazole in intermediate 1 undergoes a substitution reaction with bromine in ethyl bromide to form a quaternary ammonium salt structure to obtain intermediate 2;
[0010] Step A2: β-cyclodextrin, sodium hydroxide, N,N-dimethylformamide and dimethyl sulfoxide are mixed, and 3-bromo-1-propylene is added under stirring at a rate of 500-600 rpm and a temperature of 5°C, and the mixture is reacted for 48 hours to obtain intermediate 3; intermediate 3 is mixed with deionized water, and intermediate 2 is added under stirring at a rate of 500-600 rpm and room temperature, and the mixture is reacted for 48 hours to obtain an inclusion compound;
[0011] The ratio of β-cyclodextrin, sodium hydroxide and 3-bromo-1-propylene is 0.03-0.04 mol: 55-60 g: 0.08-0.1 mol, and the ratio of intermediate 3 to intermediate 2 is 0.03-0.04 mol: 0.03-0.04 mol;
[0012] During the reaction, the hydroxyl group in β-cyclodextrin and the bromine in 3-bromo-1-propylene undergo a substitution reaction to introduce a double bond to obtain intermediate 3. Since intermediate 3 contains a β-cyclodextrin structure and intermediate 2 contains a hydrophobic adamantane structure, during the stirring process, intermediate 2 is included in intermediate 3 to obtain an inclusion compound.
[0013] Step A3: mixing the modified copolymer, 1,3-propanedithiol and deionized water, reacting for 20-30 minutes at a stirring rate of 120-180 rpm and a temperature of 40° C., then adding the inclusion compound, and continuing the reaction for 1-2 hours to obtain a modified scale inhibitor;
[0014] The ratio of the modified copolymer, 1,3-propanedithiol and inclusion compound is 30-40 g: 0.05-0.06 mol: 25-35 g;
[0015] During the reaction, the double bond in the modified copolymer first undergoes a click reaction with the thiol group in 1,3-propanedithiol, and then the inclusion compound is added. The double bond in the inclusion compound further undergoes a click reaction with another thiol group in 1,3-propanedithiol, and the inclusion compound is grafted onto the modified copolymer to obtain a modified corrosion inhibitor.
[0016] The modified copolymer is prepared by the following steps:
[0017] Step B1: polyetheramine, triethylamine and chloroform are mixed, and methacryloyl chloride is added under nitrogen protection at a stirring rate of 400-500 rpm and room temperature, and the mixture is reacted for 6-8 hours to obtain a terminal double-bond polyether; the terminal double-bond polyether, terminal hydrogen silicone oil and toluene are mixed, and Custer catalyst is added under nitrogen protection at a stirring rate of 400-500 rpm and a temperature of 100° C., and the mixture is reacted for 3-4 hours to obtain a block polyether;
[0018] The usage ratio of polyetheramine, triethylamine and methacryloyl chloride is 35-40g: 5-6mL: 0.08-0.09mol, and the usage ratio of terminal double bond polyether, terminal hydrogen silicone oil and Custer catalyst is 40-45g: 35-40g: 3-4g;
[0019] During the reaction, the terminal amino group in the polyetheramine reacts with the acyl chloride group in methacryloyl chloride to form acyl chloride and introduce double bonds to obtain a terminal double-bond polyether. The double bonds in the terminal double-bond polyether then undergo a silylation reaction with the terminal hydrogen silicone oil to obtain a terminal double-bond block polyether.
[0020] Step B2: acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether were mixed, stirred at a stirring rate of 500-600 rpm and a temperature of 95° C., and ammonium persulfate was added, and the mixture was reacted for 24 hours to obtain a copolymer;
[0021] The usage ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, block polyether and ammonium persulfate is 0.4-0.5 mol: 0.04-0.06 mol: 70-80 g: 5-6 g;
[0022] During the reaction, under the action of ammonium persulfate, free radical polymerization occurs in the double bonds of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether to obtain a copolymer;
[0023] Step B3: Mix the copolymer, n-propanolamine and deionized water, react for 3-4 hours at a stirring rate of 400-500 rpm and a temperature of 80° C., then add methacrylic anhydride, triethylamine and N,N-dimethylformamide, and react for 20-24 hours at a stirring rate of 400-500 rpm and a temperature of 40° C. under nitrogen protection to obtain a modified copolymer;
[0024] The usage ratio of copolymer, n-propanolamine, methacrylic anhydride and triethylamine is 30-40g: 0.05-0.06mol: 0.05-0.06mol: 2-3g;
[0025] During the reaction, the carboxyl group in the copolymer undergoes an amidation reaction with the amino group in n-propanolamine to form an amide group, and a hydroxyl group is introduced. The hydroxyl group then undergoes an esterification reaction with methacrylic anhydride under the catalysis of triethylamine to introduce a double bond to obtain a modified copolymer.
[0026] Beneficial effects of the invention: The invention relates to a phosphorus-free scale inhibitor dispersant for coal gasification ash water and a preparation method thereof. By adding a modified scale inhibitor into the scale inhibitor dispersant raw material, the problems of phosphorus content and insufficient scale inhibition performance of the existing scale inhibitor dispersant for coal gasification ash water are solved, and at the same time, the scale inhibitor has good high-temperature corrosion inhibition ability. The modified scale inhibitor is based on a modified copolymer and is connected with inclusions by covalent bonds. Since the inclusion is a host-guest structure prepared with cyclodextrin as the main body and intermediate 2 as the guest, this structure undergoes decomplexation under the high temperature conditions of coal gasification ash water to release intermediate 2, and intermediate 2 is a structure with an imidazole quaternary ammonium salt hydrophilic group at one end and a diamond hydrophobic group at the other end, so that it has good corrosion inhibition. At the same time, since it is the guest of the inclusion, it can gradually decomplex with high temperature to show a slow-release property, thereby achieving a better corrosion inhibition effect. At the same time, the inclusion that releases the guest is due to its own The cyclodextrin structure, the polar hydroxyl groups it contains can not only chelate with the metal ions in the coal gasification ash water to play a scale inhibition role, but also its hydrophobic cavity can contain metal ions, so that the modified scale inhibitor exhibits better scale inhibition performance, and the modified copolymer contains a large number of hydroxyl, carboxyl and sulfonic acid groups. The presence of these groups changes the solubility of calcium ions in the coal gasification ash water, avoiding the scaling ions from combining with the crystal nucleus to form scale. At the same time, the presence of molecular chain segments interferes with the normal development of the crystals and destroys their basic structure, thereby exerting their scale inhibition performance. By introducing silicone oil block polyether structure and sulfonic acid groups, the high temperature resistance of the modified scale inhibitor is improved to a certain extent, and the presence of these structures also improves the water solubility of the modified scale inhibitor, avoiding the bridging effect of the polymer chain on the scaling microcrystals to form insoluble gels, and further improving the dispersion effect of the modified scale inhibitor, so that it can exert better scale inhibition performance. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1 A non-phosphorus scale inhibitor and dispersant for coal gasification ash water is prepared by the following steps: weigh the following raw materials in weight percentage: 20% of commercially available Zhengzhou Chemical polyepoxy succinic acid, 10% of modified scale inhibitor and 2% of zinc sulfate, and the balance is water, and mix the polyepoxy succinic acid, modified scale inhibitor, zinc sulfate and water to prepare a non-phosphorus scale inhibitor and dispersant for coal gasification ash water;
[0029] The modified antiscalant is prepared by the following steps:
[0030] Step A1: 1-bromoadamantane, 2-methylimidazole, potassium carbonate and o-dichlorobenzene were mixed, and the mixture was reacted at a stirring rate of 300 rpm and a temperature of 180° C. for 3 h to obtain intermediate 1; intermediate 1 was mixed with ethyl bromide, and the mixture was reacted at a stirring rate of 300 rpm and a temperature of 40° C. for 24 h to obtain intermediate 2;
[0031] The ratio of 1-bromoadamantane, 2-methylimidazole and potassium carbonate is 0.05 mol: 0.1 mol: 15 g, and the ratio of intermediate 1 and ethyl bromide is 0.05 mol: 0.07 mol;
[0032] Step A2: β-cyclodextrin, sodium hydroxide, N,N-dimethylformamide and dimethyl sulfoxide were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 500 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain intermediate 3; intermediate 3 was mixed with deionized water, and intermediate 2 was added under stirring at a rate of 500 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain an inclusion compound;
[0033] The ratio of β-cyclodextrin, sodium hydroxide and 3-bromo-1-propylene is 0.03 mol: 55-60 g: 0.08 mol, and the ratio of intermediate 3 to intermediate 2 is 0.03 mol: 0.04 mol;
[0034] Step A3: the modified copolymer, 1,3-propanedithiol and deionized water were mixed, and the mixture was reacted for 30 minutes at a stirring rate of 120 rpm and a temperature of 40° C., and then the inclusion compound was added and the reaction was continued for 2 hours to obtain a modified scale inhibitor;
[0035] The ratio of the modified copolymer, 1,3-propanedithiol and inclusion compound is 30 g: 0.05 mol: 35 g;
[0036] The modified copolymer is prepared by the following steps:
[0037] Step B1: Mix commercially available PEA1000 polyetheramine, triethylamine and chloroform, stir under nitrogen protection at a stirring rate of 400 rpm, at room temperature, add methacryloyl chloride, and react for 8 hours to obtain a terminal double-bond polyether; mix the terminal double-bond polyether, commercially available M850-2000 terminal hydrogen silicone oil and toluene, stir under nitrogen protection at a stirring rate of 400 rpm, at a temperature of 100°C, add a Custer catalyst, and react for 4 hours to obtain a block polyether;
[0038] The ratio of polyetheramine, triethylamine and methacryloyl chloride is 35g:5mL:0.08mol, and the ratio of terminal double-bond polyether, terminal hydrogen silicone oil and Custer catalyst is 40g:350g:3g;
[0039] Step B2: acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether were mixed, and ammonium persulfate was added under stirring conditions of a stirring rate of 500 rpm and a temperature of 95° C., and the mixture was reacted for 24 hours to obtain a copolymer;
[0040] The usage ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, block polyether and ammonium persulfate is 0.4 mol: 0.04 mol: 70 g: 5 g;
[0041] Step B3: Mix the copolymer, n-propanolamine and deionized water, and react for 4 hours at a stirring rate of 400 rpm and a temperature of 80° C., then add methacrylic anhydride, triethylamine and N,N-dimethylformamide, and react for 24 hours at a stirring rate of 400 rpm and a temperature of 40° C. under nitrogen protection to obtain a modified copolymer;
[0042] The usage ratio of the copolymer, n-propanolamine, methacrylic anhydride and triethylamine is 30g:0.05mol:0.05mol:2g.
[0043] Example 2 A non-phosphorus scale inhibitor and dispersant for coal gasification ash water is prepared by the following steps: weigh the following raw materials in weight percentage: 15% of commercially available Zhengzhou Chemical polyepoxy succinic acid, 15% of modified scale inhibitor and 2% of zinc sulfate, and the balance is water, and mix the polyepoxy succinic acid, modified scale inhibitor, zinc sulfate and water to prepare a non-phosphorus scale inhibitor and dispersant for coal gasification ash water;
[0044] The modified antiscalant is prepared by the following steps:
[0045] Step A1: 1-bromoadamantane, 2-methylimidazole, potassium carbonate and o-dichlorobenzene were mixed, and the mixture was reacted for 2 h at a stirring rate of 400 rpm and a temperature of 180° C. to obtain intermediate 1; intermediate 1 was mixed with ethyl bromide, and the mixture was reacted for 20 h at a stirring rate of 400 rpm and a temperature of 40° C. to obtain intermediate 2;
[0046] The ratio of 1-bromoadamantane, 2-methylimidazole and potassium carbonate is 0.07 mol: 0.1 mol: 15 g, and the ratio of intermediate 1 and ethyl bromide is 0.07 mol: 0.05 mol;
[0047] Step A2: β-cyclodextrin, sodium hydroxide, N,N-dimethylformamide and dimethyl sulfoxide were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 600 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain intermediate 3; intermediate 3 was mixed with deionized water, and intermediate 2 was added under stirring at a rate of 600 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain an inclusion compound;
[0048] The ratio of β-cyclodextrin, sodium hydroxide and 3-bromo-1-propylene is 0.04 mol: 55 g: 0.08 mol, and the ratio of intermediate 3 to intermediate 2 is 0.04 mol: 0.03 mol;
[0049] Step A3: the modified copolymer, 1,3-propanedithiol and deionized water were mixed, and the mixture was reacted for 20 minutes at a stirring rate of 180 rpm and a temperature of 40° C., and then the inclusion compound was added and the reaction was continued for 1 hour to obtain a modified scale inhibitor;
[0050] The ratio of the modified copolymer, 1,3-propanedithiol and inclusion compound is 30 g: 0.05 mol: 25 g;
[0051] The modified copolymer is prepared by the following steps:
[0052] Step B1: Mix commercially available PEA1000 polyetheramine, triethylamine and chloroform, stir under nitrogen protection at a stirring rate of 500 rpm, at room temperature, add methacryloyl chloride, and react for 6 hours to obtain a terminal double-bond polyether; mix the terminal double-bond polyether, commercially available M850-2000 terminal hydrogen silicone oil and toluene, stir under nitrogen protection at a stirring rate of 500 rpm, at a temperature of 100°C, add a Custer catalyst, and react for 3 hours to obtain a block polyether;
[0053] The ratio of polyetheramine, triethylamine and methacryloyl chloride is 35g:6mL:0.08mol, and the ratio of terminal double bond polyether, terminal hydrogen silicone oil and Custer catalyst is 40g:35g:4g;
[0054] Step B2: acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether were mixed, stirred at a stirring rate of 600 rpm and a temperature of 95° C., and ammonium persulfate was added, and the mixture was reacted for 24 hours to obtain a copolymer;
[0055] The usage ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, block polyether and ammonium persulfate is 0.5 mol: 0.04 mol: 70 g: 6 g;
[0056] Step B3: Mix the copolymer, n-propanolamine and deionized water, and react for 3 hours at a stirring rate of 500 rpm and a temperature of 80° C., then add methacrylic anhydride, triethylamine and N,N-dimethylformamide, and react for 20 hours at a stirring rate of 500 rpm and a temperature of 40° C. under nitrogen protection to obtain a modified copolymer;
[0057] The usage ratio of the copolymer, n-propanolamine, methacrylic anhydride and triethylamine is 40g:0.05mol:0.06mol:2g.
[0058] Example 3 A non-phosphorus scale inhibitor and dispersant for coal gasification ash water is prepared by the following steps: weigh the following raw materials in weight percentage: 15% of commercially available Zhengzhou Chemical polyepoxy succinic acid, 15% of modified scale inhibitor and 3% of zinc sulfate, and the balance is water, and mix the polyepoxy succinic acid, modified scale inhibitor, zinc sulfate and water to prepare a non-phosphorus scale inhibitor and dispersant for coal gasification ash water;
[0059] The modified antiscalant is prepared by the following steps:
[0060] Step A1: 1-bromoadamantane, 2-methylimidazole, potassium carbonate and o-dichlorobenzene were mixed, and the mixture was reacted at a stirring rate of 400 rpm and a temperature of 180° C. for 3 h to obtain intermediate 1; intermediate 1 was mixed with ethyl bromide, and the mixture was reacted at a stirring rate of 400 rpm and a temperature of 40° C. for 24 h to obtain intermediate 2;
[0061] The ratio of 1-bromoadamantane, 2-methylimidazole and potassium carbonate is 0.07 mol: 0.12 mol: 18 g, and the ratio of intermediate 1 and ethyl bromide is 0.07 mol: 0.07 mol;
[0062] Step A2: β-cyclodextrin, sodium hydroxide, N,N-dimethylformamide and dimethyl sulfoxide were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 600 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain intermediate 3; intermediate 3 was mixed with deionized water, and intermediate 2 was added under stirring at a rate of 600 rpm and a temperature of 5°C, and the mixture was reacted for 48 hours to obtain an inclusion compound;
[0063] The ratio of β-cyclodextrin, sodium hydroxide and 3-bromo-1-propylene is 0.04 mol: 60 g: 0.1 mol, and the ratio of intermediate 3 to intermediate 2 is 0.04 mol: 0.04 mol;
[0064] Step A3: the modified copolymer, 1,3-propanedithiol and deionized water were mixed, and the mixture was reacted for 30 minutes at a stirring rate of 180 rpm and a temperature of 40° C., and then the inclusion compound was added and the reaction was continued for 2 hours to obtain a modified scale inhibitor;
[0065] The ratio of the modified copolymer, 1,3-propanedithiol and inclusion compound is 40g:0.06mol:35g;
[0066] The modified copolymer is prepared by the following steps:
[0067] Step B1: Mix commercially available PEA1000 polyetheramine, triethylamine and chloroform, stir under nitrogen protection at a stirring rate of 500 rpm, at room temperature, add methacryloyl chloride, and react for 8 hours to obtain a terminal double-bond polyether; mix the terminal double-bond polyether, commercially available M850-2000 terminal hydrogen silicone oil and toluene, stir under nitrogen protection at a stirring rate of 500 rpm, at a temperature of 100°C, add a Custer catalyst, and react for 4 hours to obtain a block polyether;
[0068] The ratio of polyetheramine, triethylamine and methacryloyl chloride is 40g:6mL:0.09mol, and the ratio of terminal double bond polyether, terminal hydrogen silicone oil and Custer catalyst is 45g:40g:4g;
[0069] Step B2: acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether were mixed, stirred at a stirring rate of 600 rpm and a temperature of 95° C., and ammonium persulfate was added, and the mixture was reacted for 24 hours to obtain a copolymer;
[0070] The usage ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, block polyether and ammonium persulfate is 0.5 mol: 0.06 mol: 80 g: 6 g;
[0071] Step B3: Mix the copolymer, n-propanolamine and deionized water, and react for 4 hours at a stirring rate of 500 rpm and a temperature of 80° C., then add methacrylic anhydride, triethylamine and N,N-dimethylformamide, and react for 24 hours at a stirring rate of 500 rpm and a temperature of 40° C. under nitrogen protection to obtain a modified copolymer;
[0072] The usage ratio of the copolymer, n-propanolamine, methacrylic anhydride and triethylamine is 40g:0.06mol:0.06mol:3g.
[0073] Comparative Example 1 Compared with Example 3, this comparative example replaces the inclusion compound in the preparation process of the modified scale inhibitor in Example 3 with intermediate 3, and the other steps are the same.
[0074] Comparative Example 2 Compared with Example 3, this comparative example removes 1,3-propanedithiol during the preparation of the modified scale inhibitor in Example 3, and the other steps are the same.
[0075] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that the block polyether in the preparation process of the modified copolymer of Example 3 is replaced by the terminal double-bond polyether of Example 3, and the other steps are the same.
[0076] Comparative Example 4 Compared with Example 3, this comparative example is to remove 2-acrylamide-2-methylpropanesulfonic acid in the preparation process of the modified copolymer in Example 3, and the other steps are the same.
[0077] The phosphorus-free scale inhibitor dispersant for coal gasification ash water prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 was taken, and its calcium carbonate scale inhibition performance was measured with reference to GB / T 16632-2019. The experimental water was ultrapure water. In the calcium carbonate scale inhibition experiment, the calcium ion concentration was 400 mg / L, the bicarbonate ion concentration was 800 mg / L, the temperature was 60°C, the time was 10 h, and the scale inhibitor dispersant concentration was 15 mg / L. The calcium carbonate scale inhibition rate was calculated, and then the temperature was 180°C and the pressure was 1.7 MPa. The experiment was carried out to calculate the calcium carbonate scale inhibition rate under high temperature and high pressure conditions. To evaluate its scale inhibition performance, refer to the performance of water treatment agent dispersing iron oxide, and measure its dispersing iron oxide performance by the transmittance method. Its calcium ion concentration is 150mg / L, ferrous ion concentration is 10mg / L, temperature is 50℃, time is 5h, scale inhibitor dispersant concentration is 15mg / L, and its dispersing iron oxide performance is evaluated by transmittance. Referring to GB / T 18175-2014, the static weight loss method is used to determine the corrosion inhibition rate of Q235 carbon steel specimens in water. The experimental water is tap water, the sample size is 50mm×25mm×2mm, the temperature is 70℃, the time is 72h, and the scale inhibitor dispersant concentration is 15mg / L. The corrosion inhibition rate is calculated to evaluate its corrosion inhibition performance. The test results are as follows:
[0078]
[0079]
[0080] It can be seen from the test results in the table shown that when Example 7, Example 8 and Example 9 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, the inclusion compound in the preparation process of the modified scale inhibitor of Example 3 is replaced by the intermediate 3. Due to the lack of the guest of the inclusion compound, its corrosion inhibition rate is greatly reduced. Comparative Example 2 removes 1,3-propanedithiol in the preparation process of the modified scale inhibitor of Example 3. Due to the lack of covalent bond connection between the inclusion compound and the modified copolymer, its various properties are reduced. Comparative Example 3 replaces the block polyether in the preparation process of the modified copolymer of Example 3 with the terminal double-bond polyether of Example 3. Due to the lack of silicone oil segments, its high temperature resistance is reduced. Comparative Example 4 removes 2-acrylamide-2-methylpropane sulfonic acid in the preparation process of the modified copolymer of Example 3. Due to the lack of sulfonic acid groups, its dispersion performance and scale inhibition performance are reduced.
[0081] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a phosphorus-free scale inhibitor dispersant for coal gasification ash water, characterized in that: The method comprises the following steps: weighing the following raw materials in weight percentage: 15-20% of polyepoxysuccinic acid, 10-15% of modified scale inhibitor and 2-3% of zinc sulfate, with the balance being water, and mixing the polyepoxysuccinic acid, modified scale inhibitor, zinc sulfate and water to prepare a phosphorus-free scale inhibitor dispersant for coal gasification ash water; The modified antiscalant is prepared by the following steps: Step A1: 1-bromoadamantane, 2-methylimidazole, potassium carbonate and o-dichlorobenzene are mixed, and the mixture is reacted for 2-3 hours at a stirring rate of 300-400 rpm and a temperature of 180° C. to obtain intermediate 1; intermediate 1 is mixed with ethyl bromide, and the mixture is reacted for 20-24 hours at a stirring rate of 300-400 rpm and a temperature of 40° C. to obtain intermediate 2; Step A2: β-cyclodextrin, sodium hydroxide, N,N-dimethylformamide and dimethyl sulfoxide are mixed, and 3-bromo-1-propylene is added under stirring at a rate of 500-600 rpm and a temperature of 5°C, and the mixture is reacted for 48 hours to obtain intermediate 3; intermediate 3 is mixed with deionized water, and intermediate 2 is added under stirring at a rate of 500-600 rpm and room temperature, and the mixture is reacted for 48 hours to obtain an inclusion compound; Step A3: Mix the modified copolymer, 1,3-propanedithiol and deionized water, react for 20-30 minutes at a stirring rate of 120-180 rpm and a temperature of 40° C., then add the inclusion compound and continue the reaction for 1-2 hours to obtain a modified scale inhibitor.
2. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 1, characterized in that: In step A1, the ratio of 1-bromoadamantane, 2-methylimidazole and potassium carbonate is 0.05-0.07 mol: 0.1-0.12 mol: 15-18 g, and the ratio of intermediate 1 and bromoethane is 0.05-0.07 mol: 0.05-0.07 mol.
3. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 2, characterized in that: In step A2, the ratio of β-cyclodextrin, sodium hydroxide and 3-bromo-1-propylene is 0.03-0.04 mol: 55-60 g: 0.08-0.1 mol, and the ratio of intermediate 3 to intermediate 2 is 0.03-0.04 mol: 0.03-0.04 mol.
4. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 3, characterized in that: In step A3, the ratio of the modified copolymer, 1,3-propanedithiol and inclusion compound is 30-40 g: 0.05-0.06 mol: 25-35 g.
5. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 4, characterized in that: The modified copolymer is prepared by the following steps: Step B1: polyetheramine, triethylamine and chloroform are mixed, and methacryloyl chloride is added under nitrogen protection at a stirring rate of 400-500 rpm and room temperature, and the mixture is reacted for 6-8 hours to obtain a terminal double-bond polyether; the terminal double-bond polyether, terminal hydrogen silicone oil and toluene are mixed, and Custer catalyst is added under nitrogen protection at a stirring rate of 400-500 rpm and a temperature of 100° C., and the mixture is reacted for 3-4 hours to obtain a block polyether; Step B2: acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and block polyether were mixed, stirred at a stirring rate of 500-600 rpm and a temperature of 95° C., and ammonium persulfate was added, and the mixture was reacted for 24 hours to obtain a copolymer; Step B3: Mix the copolymer, n-propanolamine and deionized water, and react for 3-4 hours at a stirring rate of 400-500 rpm and a temperature of 80°C. Then add methacrylic anhydride, triethylamine and N,N-dimethylformamide, and react for 20-24 hours at a stirring rate of 400-500 rpm and a temperature of 40°C under nitrogen protection to obtain a modified copolymer.
6. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 5, characterized in that: In step B1, the ratio of polyetheramine, triethylamine and methacryloyl chloride is 35-40 g: 5-6 mL: 0.08-0.09 mol, and the ratio of terminal double bond polyether, terminal hydrogen silicone oil and Custer catalyst is 40-45 g: 35-40 g: 3-4 g.
7. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 6, characterized in that: In step B2, the usage ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, block polyether and ammonium persulfate is 0.4-0.5 mol: 0.04-0.06 mol: 70-80 g: 5-6 g.
8. The method for preparing a phosphorus-free scale inhibitor and dispersant for coal gasification ash water according to claim 7, characterized in that: In step B3: the ratio of the copolymer, n-propanolamine, methacrylic anhydride and triethylamine is 30-40 g: 0.05-0.06 mol: 0.05-0.06 mol: 2-3 g.
9. A phosphorus-free scale inhibitor and dispersant for coal gasification ash water, characterized in that: Prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Environment-friendly type composite corrosion-inhibiting anti-sludging agent for softening water quality and circulating chilled water
CN101186396A
Preparation method of novel phosphorus-free grey water dispersing agent
CN117466449A